Doubled Haploid Technology for Genetic Improvement in Barley (Hordeum vulgare): Anther Culture and Beyond: Doubled haploid technology for barley improvement - Patial, Madhu; Bishnoi, Santosh Kumar; Singh, Om Vir; Gandhi, Silky; Thakur, Vandana; Pal, Dharam; Kumar Pramanick, Kallol (Journal of Cereal Research, 2025)
Anther culture is an important technology in plant breeding which leads to the production of haploid and doubled haploid plants. The introduction of many cultivars in barley (Hordeum vulgare) has been made possible by this technology. Genetic improvement in barley has been greatly aided by doubled haploid (DH) technology, which has made it easier to create linkage maps, perform genetic analysis, and map QTLs. Low embryogenic potential and high albino plantlet frequency are two issues that still limit the effectiveness of DH generation in some genotypes, even with several improvements made to anther culture techniques. To overcome these constraints and ensure the broad application of DH breeding in barley, more optimization is required to improve the viability of green plantlets. Key research needs will be addressed by this review, including different work done by researchers to decrease albinism, increase the effectiveness of haploid induction, and incorporate molecular techniques into DH technology. This review aims to increase DH output, broaden its use in breeding programs, and provide a more efficient framework for applying DH technology in barley research by methodically examining existing methods and suggesting creative solutions.Key words: Androgenesis, CRISPR/Cas9, doubled haploid, genomics, Hordeum vulgare